Intracellular Redox Perturbation in Saccharomyces cerevisiae Improved Furfural Tolerance and Enhanced Cellulosic Bioethanol Production - Liu, Chen-Guang; Li, Kai; Li, Ke-Yi; Sakdaronnarong, Chularat; Mehmood, Muhammad Aamer; Zhao, Xin-Qing; Bai, Feng-Wu (Frontiers in Bioengineering and Biotechnology, 2020)
Furfural is a major toxic byproduct found in the hydrolysate of lignocellulosic biomass, which adversely interferes with the growth and ethanol fermentation of Saccharomyces cerevisiae. The current study was focused on the impact of cofactor availability derived intracellular redox perturbation on furfural tolerance. Here, three strategies were employed in cofactor conversion in S. cerevisiae: (1) heterologous expression of NADH dehydrogenase (NDH) from E. coli which catalyzed the NADH to NAD+ and increased the cellular sensitivity to furfural, (2) overexpression of GLR1, OYE2, ZWF1, and IDP1 genes responsible for the interconversion of NADPH and NADP+, which enhanced the furfural tolerance, (3) expression of NAD(P)+ transhydrogenase (PNTB) and NAD+ kinase (POS5) which showed a little impact on furfural tolerance. Besides, a substantial redistribution of metabolic fluxes was also observed with the expression of cofactor-related genes. These results indicated that NADPH-based intracellular redox perturbation plays a key role in furfural tolerance, which suggested single-gene manipulation as an effective strategy for enhancing tolerance and subsequently achieving higher ethanol titer using lignocellulosic hydrolysate.